Perancangan Sistem Informasi Permintaan Kunjungan Perpustakaan Keliling Menggunakan Metode Agile Berbasis Website (Studi Kasus : Dinas Perpustakaan Dan Kearsipan Kota Tangerang Selatan) - Jumaenah, Juju; Harits, Abdurrahman (Journal of Information Systems and Business Technology, 2026)
Information systems are crucial for decision-making by providing accurate, timely, and relevant information. The purpose of this research is to create and develop an integrated and efficient website-based mobile library visit request application. Users can easily request a mobile library visit simply by filling in the required data. The system was designed using the Agile Development Method, an iterative and adaptive software development methodology. This system aims to improve service quality, request management efficiency, and information transparency. The web-based mobile library visit request information system allows all involved parties to play an active and integrated role. The process involves applicants submitting a visit request through the system, the administrator verifies the request data and schedules the visit, and the mobile library staff updates the visit status. The library service can monitor the entire request and visit process in real time through the system's tracking feature. The results of this research and development demonstrate that the mobile library visit request system can replace manual processes, manage request data, schedule visits, and generate reports in a more structured and integrated manner. It is expected to be more optimal and transparent. However, the mobile library visit request system needs to be continuously developed to be more user-friendly and tailored to user needs